2023
DOI: 10.1007/s00227-023-04235-y
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial communities associated with corals out-planted on the Great Barrier Reef are inherently dynamic over space and time

Abstract: Coral propagation and out-planting are becoming commonly adopted as part of reef stewardship strategies aimed at improving reef resilience through enhanced natural recovery and rehabilitation. The coral microbiome has a crucial role in the success of the coral holobiont and can be impacted shortly after out-planting. However, long-term characterisation of the out-plant microbiome in relation to out-plant survival, and how these properties vary across reef sites, is unexplored. Therefore, at three reef sites on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 87 publications
1
11
0
Order By: Relevance
“…For both experiments, treatment (e.g., reef, nursery 1, and nursery 2) was not identified as a confounding factor for the PERMANOVA results. Changes in coral-associated bacterial communities after transfer from native reef to coral nurseries observed in this study are consistent with previous observations for A. millepora during nursery propagation on the GBR (Strudwick et al, 2022) and are typical of this coral genus when transported between distinct environments (Haydon et al, 2021;Strudwick et al, 2023;Ziegler et al, 2019).…”
Section: Impact Of Tie-materials On Coral-associated Bacterial Commun...supporting
confidence: 92%
See 2 more Smart Citations
“…For both experiments, treatment (e.g., reef, nursery 1, and nursery 2) was not identified as a confounding factor for the PERMANOVA results. Changes in coral-associated bacterial communities after transfer from native reef to coral nurseries observed in this study are consistent with previous observations for A. millepora during nursery propagation on the GBR (Strudwick et al, 2022) and are typical of this coral genus when transported between distinct environments (Haydon et al, 2021;Strudwick et al, 2023;Ziegler et al, 2019).…”
Section: Impact Of Tie-materials On Coral-associated Bacterial Commun...supporting
confidence: 92%
“…Coral fragments were harvested from donor colonies of Acropora millepora and secured to nursery frames via three different attachment materials (Figure S2). The first experiment was conducted from August 2020-February 2021 at site 'Blue Lagoon', Opal Reef, which is subject to tidal currents due to close proximity to a deep-water channel (see Howlett et al, 2021;Suggett et al, 2019), where corals have previously been demonstrated to achieve good recovery from bleaching and storm damage (Edmondson pers. obs).…”
Section: Sampling Location and Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of dominant symbiotic bacteria (i.e., Endozoicomonas sp.) may represent a promising strategy for a faster and perhaps more stable enrichment 103 ; however, without additional inoculations, their retention may be ultimately subject to environmental changes and other variables that can influence the coral-associated microbiome 104 107 .…”
Section: Discussionmentioning
confidence: 99%
“…Survivorship of Planted CoralsAttachment and survival of coral fragments planted with Coralclip ® have been evaluated at various CNP sites on an ad hoc basis since 2019, using either (1) a rapid roving survey technique to capture Coralclip ® effectiveness of diffusely planted corals across a large area and sample size (as perSuggett et al 2020), or (2) marked fate-tracked plots to evaluate species and site-specific survivorship(Howlett et al 2022;Strudwick et al 2023). These prior fate-tracking assessments yielded coral outplant survivorship ranging 31.8-95.8% after 6-12 months (Table…”
mentioning
confidence: 99%